2018
DOI: 10.1093/ibd/izy088
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic hyperCKemia During Infliximab Therapy in Patients With Inflammatory Bowel Disease

Abstract: More than 30% of IBD patients on IFX present asymptomatic persistent and treatment-related hyperCKemia. Further relevant prospective investigation is needed. 10.1093/ibd/izy088_video1izy088.video15778459427001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Our findings are also consistent with data for other therapies with an immunosuppressant mode of action used to treat inflammatory diseases, including the JAK inhibitors baricitinib [14], upadacitinib [15][16][17], and TNFi infliximab [20]. In RA clinical studies of baricitinib [14], dose-dependent increases in CK were observed within one week, which plateaued at 8-12 weeks.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings are also consistent with data for other therapies with an immunosuppressant mode of action used to treat inflammatory diseases, including the JAK inhibitors baricitinib [14], upadacitinib [15][16][17], and TNFi infliximab [20]. In RA clinical studies of baricitinib [14], dose-dependent increases in CK were observed within one week, which plateaued at 8-12 weeks.…”
Section: Discussionsupporting
confidence: 89%
“…Elevated CK levels were among the most common AEs reported in clinical trials of upadacitinib in UC [15], ankylosing spondylitis [16], and RA [17]. In a registry study of infliximab-treated patients with IBD, 30.5% had elevated CK levels (absolute CK > 180 U/L), but none reported persistent symptoms potentially related to myopathy [20]. Other commonly used medications associated with increases in CK include antipsychotics and certain beta blockers [2], as well as statins, where CK elevations 2-10 × ULN occur in around 5% of users [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Furthermore, myositis has rarely been observed in patients treated with tumour necrosis factor (TNF) alpha inhibitors 29 and infliximab therapy is rarely associated with increased creatinine kinase levels in the blood. 30 None of our participants terminated the study due to muscle cramps or other signs of muscle alterations and only one participant in the endurance group discontinued the study due to CD-specific symptoms. These findings are consistent with previous investigations with other types of exercise programmes.…”
Section: Discussionmentioning
confidence: 91%
“…Previously, there were controversies about the safety of physical activity in CD patients, as a previous study had suggested that strenuous exercise may cause acute gastrointestinal symptoms such as heartburn and diarrhoea 28 . Furthermore, myositis has rarely been observed in patients treated with tumour necrosis factor (TNF) alpha inhibitors 29 and infliximab therapy is rarely associated with increased creatinine kinase levels in the blood 30 . None of our participants terminated the study due to muscle cramps or other signs of muscle alterations and only one participant in the endurance group discontinued the study due to CD‐specific symptoms.…”
Section: Discussionmentioning
confidence: 99%